(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article provides a comparative analysis of Albert Camus’s “The Strange” and Hamid Ismailov’s “The Dead Lake”, focusing on the philosophical, psychological, and socio-cultural dimensions that shape both narratives. While Camus’s novel exemplifies the principles of existentialism and the absurd through the emotionally detached protagonist Meursault, Ismailov’s work explores the tragic consequences of political oppression, environmental catastrophe, and the loss of innocence through the story of Yerzhan. Despite their different cultural and historical contexts—mid-20th-century French Algeria and Soviet Central Asia—both works depict protagonists who experience alienation, powerlessness, and a profound rupture between the individual and society. The comparative approach reveals shared thematic concerns such as the crisis of identity, moral ambiguity, and the confrontation between the individual and forces beyond their control. At the same time, it highlights fundamental differences in narrative style, symbolism, and philosophical orientation. This study ultimately demonstrates how both texts contribute to world literature by offering unique insights into human existence, freedom, and cultural trauma.